Menggagas Akuntansi Syari’ah: Apakah Akuntansi Islam atau Akuntansi Syari’ah Spiritual (Islam)? - Whedy Prasetyo (Akuntansi dan Teknologi Informasi, 2018)
This paper aims to explain of idea the concept spiritual shari’ah accounting. This accounting is not Islam accounting. Why is that? If religion accounting has a foundation in accordance with the law and dogmatic listed on scripture, it means that there should be no private interpretation on this dogmatic. Instead, spiritual shari’ah accounting by conscience or consensus of core ideology fused with self, others and surrounding to bring the basic beliefs and clean soul, holy and loving. The third for spiritual concepts are summarized in honesty and harmony. Spiritual shari’ah accounting concept like this is capable of providing belief, peace, morality, and faith. This study is a qualitative descriptive with secondary data for book, results of research published in the form of scientific national journals nor international or opinion publik in release of the research result. The study also sought to dig up research that is not published as reasearch reports. The results of this study indicate spiritual shari'ah accounting basis rather than values, but belief. This belief is not always based on religious teachings, but rather on spiritual values, which source from scripture and conscience.